Manganese dioxide-supported silver bismuthate as an efficient electrocatalyst for oxygen reduction reaction in zinc-oxygen batteries. (10th April 2016) - Sun, Yanzhi; Yang, Meng; Pan, Junqing; Wang, Pingyuan; Li, Wei; Wan, Pingyu
Abstract: In this paper, we present a new efficient composite electrocatalyst, manganese dioxide-supported silver bismuthate (Ag4 Bi2 O5 /MnO2 ), for oxygen reduction reaction (ORR) in alkaline media. The new electrocatalyst was characterized with scanning electron microscope (SEM), powder X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). Electrochemical measurements indicate that the Ag4 Bi2 O5 /MnO2 composite is a very efficient electrocatalyst for ORR in alkaline media. The physical and electrochemical characterization results suggest that the high activity is ascribed to the support effects from MnO2 and the synergetic effects among Ag4 Bi2 O5 and MnO2 . The analysis of rotating disk electrode (RDE) results shows that the ORR occurs via a four-electron pathway on the surface of the Ag4 Bi2 O5 /MnO2 electrocatalyst. This electrocatalyst was further tested in a designed zinc–oxygen (Zn–O2 ) battery. This battery can offer a discharge time of 225 h at 120 mA cm −2, increasing by more than 492% as compared with pure MnO2 electrocatalyst. It demonstrates that this inexpensive Ag4 Bi2 O5 /MnO2 electrocatalyst is a viable alternative to platinum electrocatalyst for energy conversion devices.